Examining information disclosure behavior on social network sites using protection motivation theory, trust and risk - Salleh , Norsaremah; Hussein, Ramlah; Mohamed, Norshidah; Abdul Karim, Nor Shahriza; Ahlan, Abdul Rahman; Aditiawarman, Umar (IBIMA Publishing, 2012)
This paper reports on an empirical study that investigates the information disclosure behavior on Social Network Sites (SNS) focusing on undergraduate University students as our population. Although much have been reported on the issue of information privacy or privacy leakage on SNS, very few have employed the Protection Motivation Theory (PMT) as a framework to understand SNS user’s behavior related to information disclosure. In this study, the PMT incorporated with trust and risk factor, has revealed that trust on SNS and perceived benefits influenced information disclosure behaviour. Our findings showed that all PMT constructs are significantly related to privacy concern. However, privacy concern and perceived risk were found not related to information disclosure behaviour. Using self-administered questionnaire, 486 undergraduate students from five different universities in Malaysia were involved in this study.